IMPLEMENTASI STRATEGI PETA KONSEP DALAM MENINGKATKAN PROSES PEMBELAJARAN DAN HASIL BELAJAR IPS KELAS VA SD NEGERI 163 PEKANBARU - Leni Maryam Maryam; Gustimal Witri Witri; Eddy Noviana Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The research carried out base on the lowly of the result of social subject in grade 5th SDN 163 Pekanbaru which is about 56,95 within minimal completeness criterion stated is 72. This research is classroom action reseac rh. The purpose of this research is to improve the quality of the learning process and learning outcomes IPS Va grade students of SD Negeri 163 Pekanbaru through the implementation of the strategy map concept into the learning process. Research carried out in May of the academic year 2014/2015 in 163 primary schools in the class Va Pekanbaru. The instrument used in this study is the teacher and student activity sheets as well as learning about the test results. This research data analysis techniques descriptive analysis techniques. This study presents an increase in the activity of teachers in the first cycle of teacher activity 61.25% with the good category, the second cycle increased to 75% in both categories, the third cycle increased to 86.25% with very good category. Student activity based on the results of research on the first cycle sbesar 65% in both categories, the second cycle increased to 73.75% with the good category and third cycle increased to 83.75% with very good category. Based on the research of student learning outcomes increased visits from the basic score 56.95 to 64 in the first cycle with peresentase increase of 12.38% from the base score, cycle II, the average value of 75.80 with a percentage increase of 33.09%, and the cycle III with an average of 79.90 with the percentage increase of the basic score of 40.30% increase learning outcomes IPS seen from mastery learning outcomes of students who reach the KKM is 72 on each daily tests. Results of this research indicate that the implementation of the map concept in the learning process IPS can improve the quality of the learning process and learning outcomes. Keywords: Strategy concept maps, and the learning process Learning Outcomes IPS